Characterization of a spatial light modulator using polarization-sensitive digital holography - Tiwari V.; Gautam S.K.; Naik D.N.; Singh R.K.; Bisht N.S. (My University, 2025)
We showa digital holographic approach for polarimetric characterization of a twisted nematic liquid crystal spatial light modulator (TNLC-SLM). An experimental scheme is designed to perform polarization analysis of the SLM with gray levels. This is realized by simultaneous detection of the polarization states of the light from the SLM for a given gray level with the help of a specially designed spatial-frequency multiplex polarization interferometer. This provides amplitude and phase characteristics of the SLM in a single shot. In order to characterize the SLM, we performJones matrix imaging at its various gray values (driving voltages), and corresponding results are presented. These results are expected to be useful in designing and developing various SLM-based experiments in the scalar and vectorial domain. © 2020 Optical Society of America.